2012
DOI: 10.1016/j.jacc.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Aortic Annular Assessment by Multidetector Computed Tomography Predicts Moderate or Severe Paravalvular Regurgitation After Transcatheter Aortic Valve Replacement

Abstract: MDCT-derived 3-dimensional aortic annular measurements are predictive of moderate or severe PAR following TAVR. Oversizing of THVs may reduce the risk of moderate or severe PAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(106 citation statements)
references
References 23 publications
3
101
1
1
Order By: Relevance
“…At present, selection of an appropriately sized prosthesis relies on echocardiographic assessment of the aortic annulus with the use of a single 2-dimensional measurement. With the use of these echocardiographic sizing recommendations approximately 1 in 9 patients undergoing TAVR is left with moderate or severe PAR, 1,3 which was shown to be an independent predictor of mortality. [4][5][6] More recently, mild PAR that was previously felt to be fairly innocuous was shown to be associated with a significant hazard for late all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, selection of an appropriately sized prosthesis relies on echocardiographic assessment of the aortic annulus with the use of a single 2-dimensional measurement. With the use of these echocardiographic sizing recommendations approximately 1 in 9 patients undergoing TAVR is left with moderate or severe PAR, 1,3 which was shown to be an independent predictor of mortality. [4][5][6] More recently, mild PAR that was previously felt to be fairly innocuous was shown to be associated with a significant hazard for late all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Given the noncircular nature of the aortic annulus, there is growing appreciation that multidetector computed tomography (MDCT), enabled by its isotropic voxels and multiplanar imaging capabilities, offers accurate, reproducible 3-dimensional annular measurements. [7][8][9] Recent data have shown that CT annular measurements are strongly predictive of PAR 3,10 ; however, to date formalized CT sizing recommendations for balloon-expandable THVs have not been proposed nor validated for routine use in TAVR. The aim of this paper is to show the rationale for the development of new CT sizing recommendations before implementation in a prospective multicenter trial.…”
Section: Introductionmentioning
confidence: 99%
“…The MSCT-based analysis of the amount and spatial distribution of aortic annulus and leaflet calcification may limit the frequency of post-implantation PVL in TAVI [58].…”
Section: Patient Screening and Qualification To Tavimentioning
confidence: 99%
“…21,22 As a result, transcatheter valve selection based on 2-dimensional imaging has resulted in the selection of THVs that are relatively undersized to the true aortic annulus, 10 potentially resulting in postdeployment PVR. [7][8][9]13 Although 3-dimensional transesophageal echocardiography may provide a better estimate of the annular dimensions, 23 MDCT is now considered the reference standard for THV sizing for both the balloon-expandable 8,11 and self-expanding 15,24,25 designs. A number of parameters, including area, 8 mean diameter, 10,11 and perimeter, 6 have been used to estimate annular dimensions and to guide approximate THV sizing.…”
Section: Value Of Mdct For Annular Sizingmentioning
confidence: 99%
“…17 Prior study has shown that undersizing of the THV may result in higher degrees of paravalvular aortic regurgitation (PVR) after balloon-expandable TAVR. [11][12][13] The self-expanding CoreValve THV differs from the balloon-expandable THV in that the CoreValve THV conforms to the native annulus, providing continuous outward radial force to the noncircular annulus. 6 Serial echocardiographic studies have shown a reduction in the degree of PVR over the year after CoreValve TAVR, 1,3 potentially because of long-term annular remodeling.…”
mentioning
confidence: 99%